2006
DOI: 10.1128/jcm.44.2.553-560.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Susceptibility Testing of Medically Important Zygomycetes by XTT Assay

Abstract: The XTT colorimetric assay quantifies fungal growth by measuring fungal metabolism and has been used successfully for susceptibility testing of Aspergillus species after 24 and 48 h of incubation. In the present study using 14 clinical isolates of Zygomycetes (Rhizopus oryzae Infections caused by Zygomycetes have emerged as an increasingly important cause of morbidity and mortality among severely immunocompromised patients, including those with hematological malignancies and hematopoietic stem cell transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 20 publications
2
53
0
Order By: Relevance
“…Data were derived from >700 fungal cells interacting with approximately 200 endothelial cells/group/experiment, with an average of 59% cells being endocytosed in the control. (B) Damage was carried out using the 96-well plate 51 Cr release method. Blocking of CotH3 and CotH2 reduced the ability of R. oryzae to cause endothelial cell damage.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Data were derived from >700 fungal cells interacting with approximately 200 endothelial cells/group/experiment, with an average of 59% cells being endocytosed in the control. (B) Damage was carried out using the 96-well plate 51 Cr release method. Blocking of CotH3 and CotH2 reduced the ability of R. oryzae to cause endothelial cell damage.…”
Section: Figurementioning
confidence: 99%
“…2 slides per arm were used for each experiment, and the experiment was performed in triplicate on different days. R. oryzae-induced endothelial or CHO cell damage was quantified using a 51 Cr release assay (48). Briefly, endothelial cells or CHO cells grown in 96-well tissue culture plates containing detachable wells were incubated with 1 μCi/well Na2 51 CrO4 (ICN) in M-199 medium (for endothelial cells) or α-MEM (for CHO cells) for 16 hours.…”
Section: Interaction Of Fungi With Endothelial or Cho Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…While fungicidal activity of posaconazole has been demonstrated against Rhizopus and Mucor spp., AmB was more rapidly fungicidal, with 95% killing noted at as early as 6 h and 99.9% killing at 24 h; for comparison, posaconazole showed less than 70% killing at 6 h and 99.9% killing at 48 h. 67 Similar observations have been made by in vitro studies using the XTT metabolic assay. 68 A few animal studies have been conducted to explore the in vivo efficacy of posaconazole in screening models of disseminated mucormycosis that used survival and/or fungal tissue burden as end points. [69][70][71][72][73] Posaconazole prolonged the survival and reduced tissue burden in neutropenic mice with disseminated Mucor infection and was as effective as standard AmB at the highest dose level.…”
Section: Posaconazolementioning
confidence: 99%
“…Since it has been shown that ASA reduces yeast flocculation, presumably by targeting oxylipin production and consequently mitochondria, these results encouraged us to investigate the changes in mitochondrial activity at the start of growth (0 h) and during the flocculent (i.e., 20 h) and less flocculent phases (i.e., 6 h) of S. cerevisiae UOFS Y-2330 35 , using the XTT reduction assay. With this assay, XTT (a tetrazolium salt) is cleaved by various mitochondrial dehydrogenases to produce coloured formazans, which are indicators of fungal metabolic activity 3,40 . We found that in S. cerevisiae UOFS Y-2330, mitochondrial activity was significantly higher (p < 0.001) during the flocculent phase (i.e., after 20 h) of growth than during the less flocculent phase (i.e., after 6 h; Fig.…”
Section: Resultsmentioning
confidence: 99%